FPGA-Based Improved Decoding Algorithm of LDPC Codes - Bao, Jian Rong; Zhang, Qian Hua; Zhang, Jian Wu (Applied Mechanics and Materials, 2014)
In this paper, a low-complexity LDPC decoder structure was proposed by optimizing the confidence propagation algorithm based on the deep space standard LDPC codes developed by the Consultative Committee for Space Data Systems (CCSDS). With the improved decoding algorithm, the structure made full use of the quasi-cyclic structure to reduce the variables in the decoder and the storage unit use for the index position of the check nodes, which saves the hardware resources greatly. Furthermore, the updating of the check nodes takes advantages of the information iterative structure of the JPL-LDPC decoder, which can reduce the computational complexity. By improving the searching methods, the computational complexity and the difficulty in FPGA implementation were reduced. The decoding performance of the decoder is close to that of the floating-point BP algorithm, which can be widely used in deep space communication with low signal-to-noise ratio.performance close to a floating-point the BP algorithm performance, can be widely used in deep space communications suitable for low signal-to-noise ratio transmission.